Structural Properties and Elemental Composition of Au+ Implanted ZnO Films, Obtained by Sol-gel Method - A.D. Pogrebnjak; T.O. Berestok; A.S. Opanasyuk; Y. Takeda; K. Oyoshi; F.F. Komarov; J. Kassi (Журнал нано- та електронної фізики)
The undoped and doped aluminum ZnO films were obtained by sol-gel method onto glass substrates with further implantation of Au+ ions. RBS, XRD methods and Raman spectroscopy were used for films characterization. The XRD analysis showed that obtained samples have a hexagonal structure with lattice constants a  0.3245-0.3249 nm, c  0.5203-0.5204 nm, c / a  1.602-1.603 and growth texture [101]. The values of coherent scattering domains (CSD) were equal to L(201)  (13.0-13.9) nm, L(101)  (12.0-12.2) nm, L(002)  (11.3-12.6) nm. It is found that there is not observed the effects of Au+ implantation on the values of CSD, lattice constants and texture of the films. According to X-ray analysis ions of gold in the films are mainly incorporated in the form of phase of AuZn3.